Analisis Perilaku Kepatuhan Penggunaan Alat Pelindung Diri (APD) Pada Tenaga Kesehatan Saat Pandemi Covid-19 (Systematic Review) - Anjlya Agustin (Universitas Dehasen Bengkulu, 2022)
Personal protective equipment (PPE) is a device that people use to protect against people who have received a disease that can be spread through contact or by other people. PPE is needed for medical personnel in order to reduce the risk of transmission of the Covid-19 virus because during the Covid-19 pandemic, the risk of increasing cases in health workers is very high because they are in direct contact with patients who have contracted Covid-19 for treatment or who are quarantined. The use of non-standard personal protective equipment is one of the reasons why health workers get Covid-19 infections. This is intended for people who work in the distribution and management of PPE, public and individual health, public health management, and providing PPE information. Before making direct contact with patients infected with the Covid-19 virus, health workers must be required to wear PPE, but the availability of PPE is very limited because it is also used by patients and the community. This condition forces health workers to reduce the use of PPE by providing health services without removing PPE for a long time or by using homemade PPE. This is what motivates academics to conduct a literature review that evaluates the factors that influence the habit of using PPE for health workers. In this study, the method used is Observational Retrospective, specifically with a qualitative approach in Systematic Review to synthesize descriptive qualitative research results using the PRISMA (Preffered Reporting Items for Systematic Review and Meta-Analysis) method, which is carried out systematically by following the steps outlined below. good and right. To get reliable and accurate results from articles that are used as references, the authors search and select scientific publications from database sources (Literature review) using Google Scholar and the search term